Serotonin Transporter Genotype Modulates the Gut Microbiota Composition in Young Rats, an Effect Augmented by Early Life Stress - El Aidy, Sahar; Ramsteijn, Anouschka S.; Dini-Andreote, Francisco; van Eijk, Roel; Houwing, Danielle J.; Salles, Joana F.; Olivier, Jocelien D. A. (Frontiers in Cellular Neuroscience, 2017)
The neurotransmitter serotonin (5-HT) plays a vital regulatory role in both the brain and gut. 5-HT is crucial for regulating mood in the brain as well as gastrointestinal motility and secretion peripherally. Alterations in 5-HT transmission have been linked to pathological symptoms in both intestinal and psychiatric disorders and selective 5-HT transporter (5-HTT) inhibitors, affecting the 5-HT system by blocking the 5-HT transporter (5-HTT) have been successfully used to treat CNS- and intestinal disorders. Humans that carry the short allele of the 5-HTT-linked polymorphic region (5-HTTLPR) are more vulnerable to adverse environmental stressors, in particular early life stress. Although, early life stress has been shown to alter the composition of the gut microbiota, it is not known whether a lower 5-HTT expression is also associated with an altered microbiome composition. To investigate this, male and female wildtype (5-HTT+/+), heterozygous (5-HTT+/-) and knockout (5-HTT-/-) 5-HT transporter rats were maternally separated for 6 hours a day from postnatal day 2 till 15. On postnatal day 21, fecal samples were collected and the impact of 5-HTT genotype and maternal separation (MS) on the microbiome was analyzed using high-throughput sequencing of the bacterial 16S rRNA gene. MS showed a shift in the ratio between the two main bacterial phyla characterized by a decrease in Bacteroidetes and an increase in Firmicutes. Interestingly, the 5-HTT genotype caused a greater microbal dysbiosis (microbial imbalance) compared with MS. A significant difference in microbiota composition was found segregating 5-HTT-/- apart from 5-HTT+/- and 5-HTT+/+ rats. Moreover, exposure of rats with 5-HTT diminished expression to MS swayed the balance of their microbiota away from homeostasis to ‘inflammatory’ type microbiota characterized by higher abundance of members of the gut microbiome including Desulfovibrio, Mucispirillum, and Fusobacterium, all of which are previously reported to be associated with a state of intestinal inflammation, including inflammation associated with MS and brain disorders like multiple depressive disorders. Overall, our data show for the first time that altered expression of 5-HTT induces disruptions in male and female rat gut microbes and these 5-HTT genotype-related disruptions are augmented when combined with early life stress.